Twilight Sparkle and the Crystal Heart Spell - Berrow, G. M. (New York : Little, Brown and Company, 2013)
"Twilight Sparkle, a very special pony and a loyal apprentice of Princess Celestia, sets off on an adventure to find the Crystal Heart Spell and learn to be a true leader"--
Accelerated Reader AR
Keywords: Ponies -- Juvenile fiction; Princesses -- Juvenile fiction; Ponies -- Fiction; Princesses -- Fiction